Molecular genetics support Gray's personality theory: the interaction of COMT and DRD2 polymorphisms predicts the behavioural approach system - Reuter, Martin; Schmitz, Anja; Corr, Philip; Hennig, Juergen (The international journal of neuropsychopharmacology, 2006)
The present study provides the first direct molecular genetics support for Gray's Reinforcement Sensitivity Theory (RST), which is one of the most influential biologically oriented personality theories. It was investigated whether the DRD2 TaqIA and the COMT polymorphisms were related to the dimensions of Gray's personality theory, as measured by the Carver and White BIS/BAS scales. In a sample of 295 healthy subjects results revealed significant DRD2×COMT interactions (i.e. epistasis) for the total BAS scale (related to positive emotionality) and for the subscales Drive (D) and Fun Seeking (FS). High BAS scores were observed if the catabolic enzyme activity and the D2 receptor density as indicated by the two polymorphisms were in disequilibrium, i.e. in the presence of the Val−/A1− (low enzyme activity/high receptor density) or the Val+/A1+ (high enzyme activity/low receptor density) alleles. In a random subsample (n=48), it could be demonstrated that those allele combinations of COMT and DRD2 associated with high BAS scores also had significantly lower prolactin levels under resting conditions, indicating high dopamine activity, compared to those allele combinations with low BAS scores. Furthermore, two-way interactions of DRD2 TaqIA×smoking status and of the Met allele of COMT×smoking status on FS and Met×gender on BIS could be shown.